THE SUSTAINABLE ENTREPRENEURSHIP INTENTION AMONG YOUNG ENTREPRENEUR - Oktaviani, Yossi
Indonesia is one of 8 developing countries that have the potential to continue to advance. In 2015 the Minister of Communication and Informatics targets that Indonesia will continue to develop from the start-up side. Efforts to link business with sustainability management have been developed into a “sustainable entrepreneurship” method, but there are indeed many obstacles that startup companies have to overcome in starting a business related to sustainable entrepreneurship. First, of course from within a young entrepreneur itself, the intention that is closely related to the formation of human behavior to analyze the relationship to the sustainability of entrepreneurship. This data collection was carried out by filling out questionnaires distributed to young entrepreneurs and 101 respondents were selected as samples in this study. The questionnaire was compiled based on intention theory (Ajzen, 2019) and sustainable entrepreneurship (Schaltegger and Wagner, 2011). With a total of 42 valid items. Then processed using SPSS 21 with multiple linear regression. The regression results show a significant and positive relationship between attitudes and sustainable entrepreneurship. Then there is a significant and positive relationship between subjective norms and sustainable entrepreneurship. Lastly, there is a significant and positive relationship between perceived behavioral control and sustainable entrepreneurship. So it can be concluded that Intention has a real relationship to sustainable entrepreneurship so that it needs to be improved and carried out if young entrepreneurs want to run a business that is not only focused on profit, but also involves the environment and people in a balanced way or what is commonly referred to as sustainable entrepreneurship. In addition, to further increase the intention to sustainable entrepreneurship, it is necessary to carry out several implementation plans for young entrepreneurs. such as environmental innovation so that a circular economy can take place from every field of business from young entrepreneurs who run.